Experimental investigations in a demonstration plant for fluidized bed gasification of multiple feedstock's in 0.5 MWth scale. (1st October 2017) - Herdel, Philipp; Krause, David; Peters, Jens; Kolmorgen, Brigga; Ströhle, Jochen; Epple, Bernd
Highlights: Commissioning with seven days of stationary HTW™ gasification. Impacts on gas composition by temperature staging within the gasifier. High temperatures within the post gasification zone lower methane content. Cold gas efficiency of 70% was reached. Low bed temperatures increase CH4 production. Abstract: The High-Temperature Winkler process (HTW TM ), which has been developed by the companies Rheinbraun and Uhde in the mid-70s of the 20th century, is an evolution of the Winkler-fluidized bed gasification process. The gasifier is divided into two zones, the bubbling fluidized bed operated at temperatures well below the ash softening point, and the freeboard operated at higher temperatures in order to decompose tars contained in the produced gas. The obtained gas may be used either in a gas turbine for power generation or for the production of fuels or chemical products. At the Institute for Energy Systems and Technology (EST) of TU Darmstadt, a semi-industrial pilot plant with thermal capacity of 0.5 MWth has been erected to test the HTW TM gasification technology for different kinds of feedstock. A fluidized bed reactor with an inner diameter of 0.4 m is used as gasifier. Gasification of the feedstock's is carried out under atmospheric pressure. The cold and the hot commissioning of the plant have successfully been conducted. This paper presents first results and experiences gained within the commissioning of the pilot plant using pre-dried lignite as feedstock.